Analisis Dampak Kebijakan Populis Terhadap Keputusan Gubernur DKI Jakarta - Aditama Candra Kusuma; Ni Wayan Widya Pratiwi; Nadya Ariska Humairah; Muhammad Raihan Yulistio (Universitas Pendidikan Nasional, 2022)
The formation of an integrated monitoring team for the provision of infiltration wells is a form of follow-up to the implementation of the Law on Water Resources Number 7 of 2004 which aims to monitor and control the use of groundwater in Jakarta which can cause land subsidence. The purpose of this study is to examine the legitimacy of the government's actions to limit the use of groundwater in Governor Decree (Kepgub) 279/2018 and to review how this decision impacts community rights. This research uses the normative juridical method. Sources of data are secondary data consisting of primary legal materials, secondary legal materials, and tertiary legal materials. The data analysis technique was qualitatively presented in a descriptive-analytical manner. The results of the study indicate that the government's action to form a supervisory team as an effort to deal with land subsidence in Jakarta is legal to be carried out and regulated by law. However, this decision violates the rights of the community, considering that in the formation of this policy, the rights of the community have been guaranteed by the above legal sources.